PSYCHOMETRIC ANALYSIS ON ORGANIZATIONAL COMMITMENT AS ATTITUDINAL VARIABLE - Betanzos Díaz, Norma; Paz Rodríguez, Francisco (Anales de Psicología / Annals of Psychology, 2007)
Organizational commitment is a construct of high interest for psychologists organizational. Researchers focused their efforts to deter-mine its conceptualization and measure, however there are signs that evidence the existence of differences. This work adopts the Peiro and Prieto´s proposal (1996), where the attitudinal slope of the commitment is emphasized. A review of reported dimensions and used instruments was made. A bank of reagents of these variables was selected and they were grouped in three scales: affective commitment, continuity commitment and implication. The factorial structure and internal consistency from the answers of 369 employees of a of telecommunications company were analyzed. Three empirical factors were showed trought exploratory facto-rial analysis. With an second order factorial analysis, these factors were grouped in a macrofactor that has a value of 2.2, this explained the 71.8% of the variance and showed an adecuated consistency (α = 0.80). This factor was denominated organizational commitment and represents the state in which the worker self identifies and extends an affective league with the organization, with its goals, and wishes to continue being a mem-ber of it. Sharing the triple component of attitudinal variables: Cognition, affect and behavior.